Co-creation of services: an online network perspective. Issue 3 (24th August 2021) - Bidar, Reihaneh; Barros, Alistair; Watson, Jason
Abstract : Purpose: In the co-creation process from a network perspective, service is produced, designed, and evaluated entirely by the actors with dynamic roles and with less participation by the firm's employees in the service process. The purpose of this paper is to develop a theoretical model that represents environmental stimuli and value perceptions that contribute to service co-creation behaviour in an online network. Design/methodology/approach: A total of 36 semi-structured interviews were conducted with members of two online programming communities – GitHub and Stack Overflow co-creators, with the data analysed using thematic analysis. The stimulus-organism-response model guided the development of the final model. Findings: Social influence and trust are influential in actor value perceptions, including primary and network value, the interplay of which leads actors to co-production, supportive, and administrative behaviour. Environmental factors do not directly drive actors; rather it is the value that initiates and drives actors, which, by extension, initiates and drives the co-creation of services. Research limitations/implications: The service co-creation behaviour model provides a basis for future research in the co-creation and co-destruction context to model behaviours within the online network organisation setting and thereby enable improvement of such systems. This model can be operationalised in a network environment through design features. Originality/value: This paper provides a rich understanding of environmental stimuli and value perception factors that contribute to the co-creation of services, and identifies different types of behaviours in dynamic online networks. This paper presents a new model of different types of behaviours emerging from actor participation in the co-creation process.